The Influence of Chatbots, Product Reviews on Purchase Decisions Through Psychological Responses as an Intervening Variable (Case Study on Shopee Users in Malang City) - Yoswiltiani Darung; Muhamamd Rifa'i; Imam Hidayat (International Journal of Management and Business, 2026)
E-commerce has grown rapidly, encouraging companies to innovate in improving the quality of service and information by utilizing digital technology, one of which is the use of chatbots and product reviews. This study aims to determine the Influence of Chatbots and Product Reviews on Purchasing Decisions through Psychological Responses as Intervening ​​Variables on Shopee Users in Malang City. In this study used 97 respondents who use the Shopee application who have interacted with Chatbot. The sampling technique used purposive sampling. Data were collected using a questionnaire. The data analysis technique in this study is Path Analysis using SmartPls version 4.0. The results of the study indicate that chatbots and product reviews have a positive and significant effect on psychological responses and a positive and significant effect on purchasing decisions, in addition psychological responses do not have a positive and significant effect on purchasing decisions. From these findings, it is identified that psychological responses have not been able to mediate the relationship between chatbots and product reviews on purchasing decisions.